TRANSLATING CULTURAL SYMBOLS INTO STUDIO LEARNING: A P–E–F FRAMEWORK FOR 3D HERITAGE TASKS TO ENHANCE MOTIVATION AND ENGAGEMENT IN HIGHER EDUCATION - Jing , Zhong; Zainuddin , Nasaie; Sulaiman , Shahrunizam; Mustapha, Azwady (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Younger learners’ engagement with Miao Traditional Festival Costumes (MTFCs) remains low because existing digital work rarely links cultural grammar to classroom-ready 3D tasks. This paper addresses that gap by consolidating four design principles (hierarchy, symmetry, repetition, ritual orientation) and five design elements (pattern, colour, structure, material, wearing) into a unified P–E–F core, then extending it with a P–E–F–M–E pathway that translates directly into studio assignments and rubrics. A systematic content analysis of 52 sources (2000–2024) shows stable consensus on principles (e.g., ritual orientation: 80.8%; symmetry: 73.1%) and elements (pattern and colour: 90.4%), providing reliable anchors for task design. We package the outputs as parameterised prompts for CLO3D/Unity, a two-axis rubric (cultural fidelity × learning outcomes), and low-cost evidence options (two 5-item mini-scales plus a short reflective note) for adoption without specialised labs. The contribution is a curriculum-ready blueprint that operationalises semiotic structure into reproducible modelling operations and student-centred evaluation. While no user testing is reported in this paper, we provide a clear route for subsequent classroom validation focused on motivation, perceived usability, and affective uptake.